The de Jong Gierveld Loneliness Scale used with Norwegian club- house members: Psychometric properties and associated factors - Bonsaksen , Tore; Opseth , Thea M.; Misund, Aud R.; Geirdal , Amy Ø.; Fekete , Orsolya R.; Nordli, Hege (International Journal of Psychosocial Rehabilitation, 2018)
Background: Loneliness is considered a common experience, but persistent loneliness can set the stage for de- pression and in other ways jeopardize psychological well-being. Loneliness appears to be particularly frequent among persons with mental health problems, and a short, feasible, and psychometrically sound measure of loneliness can assist in addressing loneliness in mental health practice and research. Aims: To contribute to the validation of a Norwegian version of the six-item de Jong Gierveld Loneliness Scale. We empirically investigated the factor structure and internal consistency of the scale, and explored factors associated with the resulting scales. Method: Ninety-four Norwegian clubhouse members completed the loneliness scale as part of a larger member survey in 2016. Factor structure was examined with Principal Components Analysis, in conjunction with Paral- lel Analysis, and internal consistency was examined with Cronbach’s coefficient alpha. Results: Two factors were extracted from the data, explaining 68.2 % of the total data variance. The structure matrix showed no cross-loadings, and all items loaded substantially (0.74-0.91) on the proposed factor. Internal consistency of the items belonging to factor 1 (social loneliness) and factor 2 (emotional loneliness) was α =0.86 and 0.63, respectively. No variables showed a significant relationship with any of the scales. Conclusions: The scale demonstrated the theoretically proposed two-factor structure, with good measures of internal consistency. Thus, the de Jong Gierveld Loneliness Scale appears promising for future use in psychosocial settings in Norway.